Can Chromatin Accessibility be Exploited for Axon Regeneration?. Issue 10 (27th August 2018) - Danzi, Matt C.; O'Neill, Nick; Bixby, John L.; Lemmon, Vance P.
Abstract: Several studies have demonstrated that the intrinsic ability of neurons to regenerate their axons can be stimulated by maneuvers that favor the open state of chromatin, such as inhibiting histone deacetylase activity or increasing histone acetyltransferase activity. Taken together, these experiments suggest that axon regenerative ability can be increased by promoting chromatin accessibility. In this article, we assess the direct evidence in the literature for this hypothesis and re‐examine other axon regeneration‐promoting manipulations to see if they provide additional support. We find that several interventions known to enhance intrinsic axonal growth capability also increase chromatin accessibility. Although the support for this correlation is strong in the literature, we conclude with a word of caution about therapeutics attempting to exploit this relationship.